(untitled) (International Journal of Natural Sciences, 2016)
The study was conducted to identify the socio-economic status of the poultry farmers and economic analysis of poultry farming at Gazipur, Bangladesh. A Total of 40 poultry farms (20 broilers and 20 layers) were selected. The farmers and farming were evaluated through the analysis of data that were collected in a pre-structured questionnaire. This study revealed that comparatively rich farmers (42.5% had >4.94 acre of land) were involved in farming. There were significant variations (p<0.05) in source of investment (57.5% own, 32.5% bank loan, 7.5% from money lenders with interest and 5% from money lenders without interest), training (72.5% not received and 27.5% received), farming as an occupation for the farmers (55% main and 45% subsidiary occupation), amount of loan taken (50% have loan and 50% have no loan), level of educational knowledge (62.5% poor, 25% medium and 23.5 % high), sources of drinking water (87.5% have own tube-well), latrine condition (67.5% have sanitary latrine) and health status of the farmers (30% good, 50% medium and 20% poor). There were no significant variation (p>0.05) in farm size and management skills of the farmers. The average number of children per farmer attends to primary school, high school, college and university were 0.7, 0.75, 0.1 and 0.01 in case of boys and 0.5, 0.45, 0.07 and 0.01 in case of girls, respectively. Per bird average annual rearing cost, return, and cost benefit ratio were 925.5 BDT., 1080 BDT. and 1:1.17 in broiler and 1332.5 BDT., 2210 BDT. and 1:1.66 in layer, respectively. This study recommends although initial investment is higher; layer farming is more profitable than broiler. International Journal of Natural Sciences (2014), 4(2) 8-12